Balanced Genome Triplication in Wheat Causes Premature Growth Arrest and an Upheaval of Genome-Wide Gene Regulation - Gou, Xiaowan; Lv, Ruili; Wang, Changyi; Fu, Tiansi; Sha, Yan; Gong, Lei; Zhang, Huakun; Liu, Bao (Frontiers in Genetics, 2020)
Polyploidy, or whole genome doubling (WGD), is a driving evolutionary force across the tree of life, and has played a pervasive role in evolution of the plant kingdom. It is generally believed that a major genetic attribute contributing to the success of polyploidy is increased gene and genome dosage. The evolution of polyploid wheat have lent support to this scenario. Wheat has evolved at three ploidal levels, diploidy, tetraploidy and hexaploidy. Ample evidence testifies that the evolutionary success, be it in respect of evolvability, natural adaptability or domestication, has dramatically increased with each elevation of the ploidal levels. A longstanding question is what would be the outcome if a further elevation of ploidy is superimposed on hexaploid wheat? Here, we characterized a spontaneously occurred nonuploid wheat individual in selfed progenies of synthetic hexaploid wheat, and compared it with its isogenic hexaploid siblings at the phenotypic, cytological and genome-wide gene expression levels. The nonuploid manifested severe defect in growth and development albeit with a balanced triplication of the three wheat subgenomes. Transcriptomic profiling of the 2nd leaf of nonuploid, taken at a stage when phenotypic abnormality was not yet discernible, already revealed significant dysregulation in global-scale gene expression, with ca. 25.2% of the 49,436 expressed genes being differentially expressed genes (DEGs) at a 2-fold change cutoff relative to the hexaploid counterpart. Both up- and down-regulated DEGs were identified in the nonuploid vs. hexaploid, including 457 genes showing qualitative alteration, i.e., silencing or activation. Impaired functionality at both cellular and organismal levels was inferred from gene ontology analysis of the DEGs. Homoeologous expression analysis of 9,574 sets of syntenic triads indicated that compared with hexaploid, the proportions showing various homeologous expression patterns were highly conserved in the nonuploid, although gene identity showed moderate reshuffling among some of the patterns in the nonuploid. Together, our results suggest hexaploidy is likely the upper limit of ploidy level in wheat; crossing this threshold incurs severe ploidy syndrome that is preceded by disruptive dysregulation of global gene expression.